Disinfection By-Products Precursors Removal By Simultaneous Coagulation And Disinfection In River Water - Naserun, Nur Izzati (Universiti Sains Malaysia, 2018)
Water was the most important component in our evolution and daily lives. Depletion of clean water supply due to presence of toxic chemicals and harmful bacteria may expose living things to waterborne diseases caused from the consumption of contaminated water. Disinfection in drinking water had significantly reduces the risk of pathogenic diseases but may cause chemical threat to human health due to disinfection by-products (DBPs) formation in the presence of natural organic matter (NOM) in water. The presence of NOM had caused many problems in drinking water, which can be removed by several treatment options such as coagulation. The main objective of this research is to study the ability of DBPs precursors removal when combining coagulation and disinfection process. This study was divided into two parts; the first part involved the comparison between effectiveness of two ferric-based coagulants for coagulation process while the second part involved the efficiency of DBPs precursors removal by using simultaneous coagulation and disinfection. Selected water quality parameters such as turbidity, UV254, colour and dissolved organic carbon (DOC) were tested for raw and treated water samples to observe the DBPs precursors removal. The coagulants used in this study were ferric chloride (FeCl3) and ferric sulphate (Fe2(SO4)3) while chlorine (Cl2) and chlorine dioxide (ClO2) were used as disinfectants. Based on the study, the highest percentage of turbidity removal was 98.03% with FeCl3 dosage at 20mg/L and pH condition 6.0. Best UV254 removal was achieved at 20 mg/L FeCl3 dosage with pH condition 6.0 (87.91% removal). The optimum colour reduction was found to be 98.92% at pH 5.0 with FeCl3 dosage of 10 mg/L. FeCl3 was proven to be a better coagulant compared to Fe2(SO4)3 in removing DBPs precursors, when used alone. According to the result from the second part of this study, the combination between FeCl3 as coagulant and Cl2 as disinfectant had the highest turbidity and UV254 removal at 97.11% and 79% respectively. However, the combination between Fe2(SO4)3 and Cl2 had the highest DOC removal from the water sample at 25.5%. The combination between FeCl3 and Cl2 resulted in the highest turbidity and UV254 removal while the combination between Fe2(SO4)3 and Cl2 had the highest DOC removal from the water sample.